On the Use of Nonfinancial Performance Measures in Management Compensation - Dirk Sliwka (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
It is often claimed that (i) managers work too hard on operational issues and do not spend enough effort on strategic activities and (ii) something can be done about this by introducing nonfinancial performance measures as for instance with a balanced scorecard. We give an explanation for both claims in a formal model. The distortion towards operational effort arises, because with financial performance measures strategic effort can only be rewarded in the future. But renegotiation-proof long term compensation plans entail too weak variable components in the future. This problem can be reduced by introducing performance measures that help to disentangle strategic and operational effects.
Keywords: D23; J33; M41; M12; 330; Performance Measurement; Nonfinancial Measures; Balanced Scorecard; Incentives; Renegotiation